Can Green Power Save Us from Climate Change? - M. Scott Taylor (Swiss Journal of Economics and Statistics, 2014)
International efforts to lower emissions have largely failed, and many now believe we will fail to limit warming to less than 2 degrees Celsius by 2100. In this extended abstract, I discuss whether a wholesale movement to renewable energy or Green Power could limit carbon emissions to meet a 2 degree Celsius target while simultaneously meeting the world's growing demands for energy. Using a very simple growth model I calculate the burden Green Power must carry in order to keep emissions within the 2 degree target, and then discuss the speed, scope, and size of the energy transition this would imply. An energy transition of sufficient speed and magnitude to meet these targets is unlikely, leading me to believe that Green Power cannot save us from climate change.
Keywords: Q42; Q47; Q54; 330; environment; carbon emissions; energy transition